Human capital, productivity, and labor allocation in rural Pakistan - Fafchamps, Marcel; Quisumbing, Agnes R. (JSTOR, 1999)
This paper investigates whether human capital affects the productivity and labor allocation of rural households in four districts of Pakistan. We find that households with better educated males earn higher off-farm income and divert labor resources away from farm activities toward nonfarm work. Education has no significant effect on productivity in crop and livestock production. The effect of human capital on household incomes is partly realized through the reallocation of labor from low productivity activities to nonfarm work. Female education and nutrition do not affect productivity and labor allocation in any systematic fashion, consistent with the marginal role women play in market oriented activities in Pakistan. As a by-product, our estimation approach also tests the existence of perfect labor and factor markets; this hypothesis is strongly rejected.